Maximum elongation degradation model and service life prediction for HTPB propellant under constant strain and chemical aging effects - Tingjing Geng; Hongfu Qiang; Heyang Miao; Xueren Wang; Zhejun Wang; Huimin Zhang (Polymer Testing)
To accurately predict the service life of the hydroxy-terminated polybutadiene (HTPB) propellant, in this study, we constructed a maximum elongation degradation model that comprehensively considers physical damage and chemical aging effects. Specifically, we conducted accelerated thermal aging and uniaxial tensile tests under different constant strain conditions to obtain performance degradation datasets. Additionally, a new degradation performance characterization model was proposed, which was validated and improved based on the correlation between the Williams-Landel-Ferry (WLF) and Arrhenius equation parameters. Finally, we performed HTPB propellant service life prediction and verification for the proposed model based on the performance data under natural storage for 22 and 26 y, and compared our results with those of traditional methods. The prediction results of the improved model were more consistent with the natural storage estimated results compared to the traditional model, with a relative error of only 7.5 % and an accuracy improvement of 75 %. This study serves as a reference for efficient resource allocation and equipment maintenance planning, thus effectively avoiding economic losses caused by resource wastage.